Mobility Characteristics of Children with Spastic Paraplegia Due to a Mutation in the KIF1A Gene - Van Beusichem, A.E.; Nicolai, J.; Verhoeven, J.; Speth, L.; Coenen, M.; Willemsen, M.A.; Kamsteeg, E.J.; Stumpel, C.; Vermeulen, R.J. (Neuropediatrics, 2020)
Several de novo variants in the KIF1A gene have been reported to cause a complicated form of hereditary spastic paraplegia. Additional symptoms include cognitive impairment and varying degrees of peripheral neuropathy, epilepsy, decreased visual acuity, and ataxia. We describe four patients (ages 10–18 years), focusing on their mobility and gait characteristics. Two patients were not able to walk without assistance and showed a severe abnormal gait pattern, crouch gait. At examination, severe contractures were found.In addition to describing the different phenotypes with specific attention to gait in our cases, we reviewed known KIF1A mutations and summarized their associated phenotypes.We conclude that mobility and cognition are severely affected in children with spastic paraplegia due to de novo KIF1A mutations. Deterioration in mobility is most likely due to progressive spasticity, muscle weakness, and the secondary development of severe contractures, possibly combined with an additional progressive polyneuropathy. Close follow-up and treatment of these patients are warranted.
Keywords: KIF1A; hereditary spastic paraplegia; spasticity; mobility; peripheral neuropathy; gait analysis